Macrocycles in Bioinspired Catalysis: From Molecules to Materials - Shang, Jie; Liu, Yao; Pan, Tiezheng (Frontiers in Chemistry, 2021)
Macrocyclic compounds have been studied extensively as the host molecules in supramolecular chemistry. Their structural characteristics make macrocycles desirable in the field of molecular recognition, which is the key to high catalytic efficiencies of natural enzymes. Therefore, macrocycles are ideal building blocks for the design of bioinspired catalysts. This mini review highlights recent advances ranging from single-molecule to metal-organic framework materials, exhibiting multilevel macrocycle catalysts with unique catalytic centers and substrate-binding affinities.